2019
DOI: 10.1016/j.conbuildmat.2019.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane reinforced ballasted track: Review, innovation and challenge

Abstract: During the development for railway, ballasted track is dominant structure and makes up more than 95% of the whole track modes. However, its shortage is considerable in high speed railway and heavy haul system. Regarding to the ballasted railway track's defects as particle breakage, settlement, and geometry irregularity which lead to enormous maintenance and cost, Polyurethane reinforced ballasted track has shown great application prospect. This reinforcement method can settle several problems, including stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Consequently, taking into account the economic aspects, despite the higher resistance of the winged panel and due to its slight difference with the mixed panel, selecting a mixed panel can be a more economical option to provide lateral resistance. [5] frictional sleeper 65 Zakeri et al [6] steel sleepers with vertical stiffeners 140 Zakeri and Talebi [7] Utilizing new technologies in the existing railway tracks sleeper anchors 19 Sabaghi [8] polyurethane bonding method 100 ~ 184 Jing et al [9] under sleeper pads 20 Pucillo et al [10] baby gabion 40 Darkhosh [12] geogrid 29 ~ 42 Esmaeili et al [13] Changing track geometry and maintenance plan increasing ballast shoulder 15 ~ 20 Kabo [14] increasing ballast shoulder 16 ~ 22 Zakeri et al [15] tamping operation -43 Sussmann et al [16] mechanical stabilization 31 Sussmann et al [16]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, taking into account the economic aspects, despite the higher resistance of the winged panel and due to its slight difference with the mixed panel, selecting a mixed panel can be a more economical option to provide lateral resistance. [5] frictional sleeper 65 Zakeri et al [6] steel sleepers with vertical stiffeners 140 Zakeri and Talebi [7] Utilizing new technologies in the existing railway tracks sleeper anchors 19 Sabaghi [8] polyurethane bonding method 100 ~ 184 Jing et al [9] under sleeper pads 20 Pucillo et al [10] baby gabion 40 Darkhosh [12] geogrid 29 ~ 42 Esmaeili et al [13] Changing track geometry and maintenance plan increasing ballast shoulder 15 ~ 20 Kabo [14] increasing ballast shoulder 16 ~ 22 Zakeri et al [15] tamping operation -43 Sussmann et al [16] mechanical stabilization 31 Sussmann et al [16]…”
Section: Discussionmentioning
confidence: 99%
“…Sabaghi [8] did STPTs and showed that the use of sleeper anchors resulted in 19% increase in the lateral resistance. Using polyurethane bonding method [9], Under Sleeper Pads (USP) [10], geosynthetics [11], and baby gabion [12] are other cases that affect the lateral resistance. The effect of geogrid on the lateral resistances was investigated by conducting STPT and LTPT.…”
Section: B) Utilizing New Technologies In the Existing Railway Tracksmentioning
confidence: 99%
“…An emulsion-modified ballast requires a different maintenance strategy because the modification can lead to a more sustainable ballast, and therefore, to an increase in the maintenance intervals [ 98 , 99 ]. This method of stabilizing the ballast particles was first introduced by a team of researchers at Heriot-Watt University in 2004 [ 100 , 101 ].…”
Section: Review Of Case Studiesmentioning
confidence: 99%
“…The polyurethane-mixed ballast is a new type of track structure which is produced by bonding the scattered ballast particles using polyurethane binder. 1,2 Different from the conventional ballast bed, the polyurethane-mixed ballast has a good integrity due to the bonding effect between ballast particles, which has a remarkable effect on maintaining the geometry and enhancing the stability of railway tracks. 3,4 The lateral resistance is one of the key indexes to maintain the stability of the railway track.…”
Section: Introductionmentioning
confidence: 99%